2008
DOI: 10.2151/jmsj.86.245
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean Dipole Modulates the Number of Extreme Rainfall Events over India in a Warming Environment

Abstract: This study shows that high resolution rainfall data indicate an increase in number of extreme rainfall events over India in the last few decades. Unravelling the mechanism behind this increasing number of extreme rainfall events in central India is important as these intense rainfall events cause floods and related damage to the life and property of more than 400 million people living in this region. The natural disaster risk hotspots analysis projected the central Indian region as the most vulnerable region f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…Anomalous easterlies in summer and fall season can excite Indian Ocean dipole (IOD) event (Murtugudde et al 2000;Rao et al 2002). Under these circumstances, the frequency of IOD events increases (Ajayamohan and Rao 2008). In the last two decades seven positive IOD events occurred in the Indian Ocean region (Rao et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalous easterlies in summer and fall season can excite Indian Ocean dipole (IOD) event (Murtugudde et al 2000;Rao et al 2002). Under these circumstances, the frequency of IOD events increases (Ajayamohan and Rao 2008). In the last two decades seven positive IOD events occurred in the Indian Ocean region (Rao et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Zhang et al (2009) have found that increasing trend of easterly wind anomaly and the southerly wind anomaly over the eastern equatorial Indian Ocean causes anomalous westward and northward displacements of the eastern Indian warm pool respectively and this helps in the formation of the Indian Ocean Dipole (IOD). Ajayamohan and Rao (2008) have shown that the IOD events have increased in the last decades as a result of Indian Ocean warming. Alory et al (2007) estimated the linear trends in oceanic temperature in Indian ocean, using Indian Ocean Thermal Archive (IOTA), a compilation of historical temperature data above 1,000 m in the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Similar correlation patterns are also apparent in the model runs initiated with 1982 1983 1984 1985 1986 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 On a regional scale, significant negative rainfall correlations are seen over the south-eastern and northern parts of India (Figure 6(a)), suggesting that during an El Niño event, the Indian landmass experiences below normal rainfall. However, in all the model predictions, this observed negative correlation is spread throughout the Indian landmass (Figure 6(f)-6(j)) except in predictions made using May initial conditions (Figure 6(j)), (Ashok et al, 2004;Ajayamohan and Rao, 2008). In order to examine how the model simulates the teleconnection associated with the IOD, we correlate the SST anomalies averaged over the IOD East box (90-110 ∘ E; 10 ∘ S-Equator; EIOD) with SST anomalies in the tropics (Figure 7).…”
Section: Teleconnections Of Ismr With El Niño Iod and Equinoomentioning
confidence: 90%
“…In addition to these patterns, there are observed increases in the frequency of the most extreme precipitation events (Gautam 2012;Gautam et al 2009) , with more extreme events occurring over the west coast and central and northeast India (Ajayamohan and Rao 2008;Goswami et al 2006;Singh and Sontakke 2002). Also, the frequency of short drought periods increases (Deka et al 2012).…”
Section: Precipitationmentioning
confidence: 96%